2008
DOI: 10.1097/bsd.0b013e31805fe9e1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure to the Surgeon and the Patient During Kyphoplasty

Abstract: Without eye or hand protection, the total radiation exposure dose to these areas would exceed the occupational exposure limit after 300 cases per year. Surgeons should wear lead lined glasses and keep their hands out of the radiation beam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 14 publications
2
47
0
8
Order By: Relevance
“…Ionizing radiation specifically refers to radiation waves carrying enough energy to remove electrons from atoms or molecules, thereby generating excessive free radicals capable of inducing cellular damage (8). Cellular damage from ionizing radiation has been reported for the skin, eyes, gonads, and blood, with the most important long-term concern being cytogenetic and chromosomal damage resulting in increased risk of carcinogenesis (12). This damage increases with the energy of the radiation wave and with higher frequency of exposure, limiting the potential for cell recovery (15).…”
Section: █ Discussionmentioning
confidence: 99%
“…Ionizing radiation specifically refers to radiation waves carrying enough energy to remove electrons from atoms or molecules, thereby generating excessive free radicals capable of inducing cellular damage (8). Cellular damage from ionizing radiation has been reported for the skin, eyes, gonads, and blood, with the most important long-term concern being cytogenetic and chromosomal damage resulting in increased risk of carcinogenesis (12). This damage increases with the energy of the radiation wave and with higher frequency of exposure, limiting the potential for cell recovery (15).…”
Section: █ Discussionmentioning
confidence: 99%
“…We found that radiation exposure was higher during procedures using less invasive spine approaches than an open approach. The use of protective barriers, to include a lead apron, thyroid shield, lead glasses, and lead gloves, can decrease the exposure [10,14,22,23,33,36].…”
Section: Cadaveric Studymentioning
confidence: 99%
“…Intraoperative orientation here is usually based on two-dimensional fluoroscopic imaging [2][3][4][5][6][7][8]. As the needle can only be visualised in one plane, the C-arm position must be changed repeatedly hence, the procedure is prolonged, being more incriminatory for the patient and bearing a higher risk for infection and collateral damage due to repetitive needle correction with higher radiation exposure [7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%